2018
DOI: 10.1089/jpm.2017.0386
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement Challenges and Their Relationship to Physical and Psychological Adjustment to Loss

Abstract: Assessing the challenges associated with bereavement is important to understanding barriers to bereaved individuals' adjustment. The five factors of the BCS point to potential targets for clinical intervention. Additional research on the BCS is needed, including validation in larger more diverse samples, and confirmation that reduction of these challenges is associated with less psychiatric morbidity and, specifically, symptoms of prolonged grief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Stroebe and colleagues (2014) found that guilt‐related emotions can exert CG symptoms after the loss of a loved one. Trevino and colleagues (2018) reported similar results among bereaved cancer caregivers. On the other hand, optimism can be a protective factor against CG symptoms.…”
Section: Limitationsmentioning
confidence: 67%
“…Stroebe and colleagues (2014) found that guilt‐related emotions can exert CG symptoms after the loss of a loved one. Trevino and colleagues (2018) reported similar results among bereaved cancer caregivers. On the other hand, optimism can be a protective factor against CG symptoms.…”
Section: Limitationsmentioning
confidence: 67%
“…However, loss-related distress can persist, a phenomenon referred to as complicated grief (Shear et al., 2011), which is associated with a broad range of health problems including depression and suicide (Shear, 2015). A plethora of research finds that adequate social support is a crucial aspect for coping with a loss and greatly reduces the risk for complicated grief and suicide among the bereaved (Burke, Laure, & Neimeyer, 2012; Juth, Smyth, Carey, & Lepore, 2015; Kleiman & Liu, 2013; Trevino et al., 2018).…”
mentioning
confidence: 99%
“…50 However, bereavement counselling is complex and associated with challenges, including forming a connection with other family and nonfamily members, challenges of dealing with change, accepting loss, and guilt. 51 No studies have specifically assessed bereavement counselling of relatives of patients with haematological malignancies.…”
Section: Seriesmentioning
confidence: 99%